REPRESENTASI FEMINISME DALAM LAGU K-POP “NXDE” OLEH (G)-IDLE - Tasya Febrianty (Indonesian Journal of Linguistics, 2000)
Abstract This article examines the representation of feminism in the K-Pop song "Nxde," released in 2022 by the girl group (G)I-DLE. The research employs a descriptive qualitative method to analyze the feminist themes in the song. The primary subject of this study is the song "Nxde" by (G)I-DLE, with data collection techniques including listening to and recording the music video available on the official (G)I-DLE YouTube account. The aim of this article is to uncover how feminism is depicted in "Nxde." The results reveal several key findings. Firstly, the song often portrays female subjects as sexual objects, reflecting the intricate gender power dynamics prevalent in Korean pop culture. Secondly, although "Nxde" addresses themes of sexuality, it also attempts to discourage the search for illegal pornographic content involving minors. Thirdly, the song underscores the significance of self-love and self-respect, highlighting a crucial aspect of feminism that focuses on individual female empowerment.